Iot-based Heart Signal Processing System for Driver Drowsiness Detection - Yunidar Yunidar; Melinda Melinda; Khairani Khairani; Muhammad Irhamsyah; Nurlida Basir (Tecno Scientifica Publishing, 2024)
Non-Indexed Publication